Persepsi Guru Pendidikan Agama Islam tentang Implementasi Pendidikan Karakter di Sekolah Menengah Pertama - Yusman; Yunita Sipahutar; Nurliani; Khoirul; Leli Hasanah Lubis (Insan Zenius Ilmiah, 2025)
Character education is a key focus of the national education system, particularly at the junior high school (SMP) level. Islamic Religious Education (PAI) teachers hold a strategic position in integrating character values ​​into the learning process, both in and outside the classroom. This study aims to analyze PAI teachers' perceptions of the implementation of character education in junior high schools. The research method used is a desk study by analyzing literature related to character education, the role of teachers, and the implementation of Islamic values ​​in schools. The results show that most PAI teachers view character education as an integral part of the mission of Islamic education, as it not only teaches cognitive aspects but also shapes students' attitudes, morals, and spirituality. However, teachers also face several challenges, such as time constraints, the influence of the digital environment, and a lack of support from some parents. This study confirms that the implementation of character education will be effective if PAI teachers are given adequate space to integrate Islamic values ​​into the curriculum, receive institutional support, and build collaboration with all involved parties.